Seasonal Changes on PM2.5 Concentrations and Emissions at Urban Hotspots in the Greater Athens Area, Greece - Kyriaki-Maria Fameli; Komninos Dionysis; Vasiliki Assimakopoulos (Environmental Sciences Proceedings, 2023)
At highly populated areas, such as the Greater Athens Area in Greece, the air quality differs significantly from one municipality to another, being highly affected by the local anthropogenic sources (traffic, residential heating, navigation) and consequent emissions. Thus, the existence of a dense network of low-cost air quality sensors provides evidence of seasonal patterns on particulate concentrations within the urban zone. In the present study, hourly PM2.5 concentrations recorded using low-cost sensors at six municipalities in the Greater Athens Area (Vrilissia, Psychiko, Peristeri, Rentis, Agia Varvara, Palaio Faliro) with different characteristics (population density, pollutant sources, surrounding land use) were collected for the year 2022. The highest mean seasonal values were recorded in the western and southern suburbs (Peristeri, Rentis and Palaio Faliro) during the cold period (winter of the year 2022). Mean concentrations decreased significantly in spring; the mean concentrations were 31.3 μg/m3 and 18.5 μg/m3 in Vrilissia in winter and spring, respectively (year: 2022).